Strengthening Competitiveness through Sharia-Based Digitalization: A Case Study of Kampung Tahu Binjai City Indonesia - Hendra Hendra; Zunaida Riska; Andri Soemitra; Faisal Nasution (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the role of digitalization in enhancing the competitiveness of sharia-based creative industries, identify the challenges faced, and formulate strategies to optimize digital transformation in the tofu production center of Kampung Tahu, Binjai City. Using a qualitative approach with a case study method, data were collected through in-depth interviews with twelve informants, field observations, and document analysis related to digitalization and sharia economic policies. Thematic analysis with an inductive approach was employed to process the data, supported by triangulation for validity. The findings reveal that digitalization contributes significantly to expanding market access, improving operational efficiency, and reinforcing sharia principles through transparent and halal-compliant financial systems. However, challenges remain, including low digital literacy, limited infrastructure, weak understanding of digital sharia practices, and insufficient institutional support. To address these, several strategies are proposed, such as sharia-based digital literacy programs, equitable infrastructure development, multi-stakeholder collaboration, and the establishment of halal digital ecosystems. This research provides a unique contribution by presenting a contextual model of sharia-oriented digitalization strategies for traditional food-based MSMEs, an area rarely explored in existing literature, thereby offering both theoretical enrichment and practical guidance for inclusive and sustainable sharia economic transformation.